1993
DOI: 10.1073/pnas.90.14.6786
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor and transforming growth factor alpha specifically induce the activation- and hyperproliferation-associated keratins 6 and 16.

Abstract: Epidermal inUury results in activation of keratinocytes which produce and respond to growth factors and cytokines and become migratory. Activated keratinocytes express a specific pair of keratin proteins, K6 and K16, distinct from the keratins in the healthy epidermis. Keratinocytes can be activated, for example, by binding ofthe appropriate ligands to the epidermal growth factor receptor (EGFR). We have analyzed the effects of EGFR activation on keratin gene transcription by transfecting DNAs containing kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
3
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 30 publications
7
122
3
1
Order By: Relevance
“…9B (60)), which means that AP1 transcription factors play no role in the signaling by TNF␣. Parenthetically, the responsiveness to EGF parallels the responsiveness to AP1, suggesting that AP1 transcription factors convey the EGF signal (18). Thus, the TNF␣-and the EGF-responsive elements in the K6b promoter DNA are distinct and independent.…”
Section: Tnf␣ Activates the K6b Promoter Through Nfb And C/ebp␤ Transmentioning
confidence: 94%
See 2 more Smart Citations
“…9B (60)), which means that AP1 transcription factors play no role in the signaling by TNF␣. Parenthetically, the responsiveness to EGF parallels the responsiveness to AP1, suggesting that AP1 transcription factors convey the EGF signal (18). Thus, the TNF␣-and the EGF-responsive elements in the K6b promoter DNA are distinct and independent.…”
Section: Tnf␣ Activates the K6b Promoter Through Nfb And C/ebp␤ Transmentioning
confidence: 94%
“…DNA Constructs-The plasmids containing keratin promoters and the control plasmids pRSVZ have been described previously (17,18,60). The plasmids containing the IL-8 promoter and (NFB)3-CAT were gifts from J. Vilcek (52); and those expressing NFB proteins were from A. Beg and D. Baltimore (35); those expressing C/EBP␤ were from S. Chen-Kiang (61); IB and His-NFB were from S. Ghosh (62,63), and CHOP was from D. Ron (64).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the accumulation of K6, K16, and K17, the protein levels of K1 and K10 are decreased (Mansbridge and Knapp, 1987;Paladini et al, 1996). First insights into the regulation of the K6 induction in wound healing came from in vitro studies with the use of human skin keratinocytes, which revealed AP-1 and epidermal growth factor-responsive elements in the human and bovine K6 promoter region (Jiang et al, 1993;Navarro et al, 1995). Epidermal growth factor receptor signaling was found to be rapidly induced after injury (Martin and Nobes, 1992;Martin, 1997).…”
mentioning
confidence: 99%
“…Diversos autores já observaram a presença de grandes quantidades de TGF-∝ nas células do colesteatoma. O TGF-∝ é uma citocina que aumenta a transcrição do gene da citoqueratina 16, ativando a proliferação dos queratinócitos 10 . Além do TGF-∝, várias outras citocinas têm sido demonstradas em grandes quantidades no colesteatoma da orelha média, quando comparado à epiderme do meato acústico externo.…”
Section: Quanto àS Características Histológicas E Imunohistoquímicas unclassified